Zimbabwe : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Zimbabwe. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This 2019 Article IV Consultation focuses on Zimbabwe's near- and medium-term challenges and policy priorities and was prepared before COVID-19 became a global pandemic that has resulted in unprecedented strains in global trade, commodity, and financial markets. It, therefore, does not reflect the implications of these developments and related policy priorities. The outbreak has greatly amplified uncertainty and downside risks around the outlook. The IMF staff is closely monitoring the situation and will continue to work on assessing its impact and the related policy response in Zimbabwe and globally. With another poor harvest expected, growth in 2020 is projected at near zero, following a sharp contraction in 2019, with food shortages continuing. With no progress on clearing longstanding external arrears, the authorities face a difficult balance of pursuing tight monetary, to reduce very high inflation, and fiscal policies to address the macroeconomic imbalances and build confidence in the currency, while averting a crisis. Pressures are mounting to increase spending on wages and for social protection to mitigate the impact of the weather shocks and high inflation. While the 2020 budget includes a significant increase in social spending, it is likely insufficient to meet the pressing needs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet